2011
DOI: 10.3858/emm.2011.43.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Induction of steroid sulfatase expression by tumor necrosis factor-α through phosphatidylinositol 3-kinase/Akt signaling pathway in PC-3 human prostate cancer cells

Abstract: Steroid sulfatase (STS) is responsible for the hydrolysis of aryl and alkyl steroid sulfates and has a pivotal role in regulating the formation of biologically active estrogens. STS may be considered a new promising drug target for treating estrogen-mediated carcinogenesis. However, the molecular mechanism of STS expression is not well-known. To investigate whether tumor necrosis factor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…In addition to the potential for estrogens to regulate STS activity, the proinflammatory cytokines IL-6 and TNFα alter STS enzyme kinetics. MCF7 cells increase STS activity in response to IL-6 and TNFα without alteration in STS mRNA levels ( 57 , 58 ), a trait also noted in other cancer cell lines ( 59 ). This suggests that post-translational modifications, possibly via STS glycosylation, are involved in regulating STS activity ( 17 , 60 , 61 ).…”
Section: Steroid Sulfatasesmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition to the potential for estrogens to regulate STS activity, the proinflammatory cytokines IL-6 and TNFα alter STS enzyme kinetics. MCF7 cells increase STS activity in response to IL-6 and TNFα without alteration in STS mRNA levels ( 57 , 58 ), a trait also noted in other cancer cell lines ( 59 ). This suggests that post-translational modifications, possibly via STS glycosylation, are involved in regulating STS activity ( 17 , 60 , 61 ).…”
Section: Steroid Sulfatasesmentioning
confidence: 70%
“…Knockdown of SULT1B1 in LNCaP cells increases DHEA-induced proliferation ( 326 ), implying that the STS/SULT1B1 ratio in the prostate regulates DHEAS/DHEA-induced proliferation. This ratio is likely to be influenced by local inflammatory conditions, as shown by Suh et al ( 59 ) who assessed whether TNFα can induce STS expression; LNCap and PC-3 cells up-regulated STS expression in a TNFα concentration and time-dependent manner. They further demonstrated that at least part of this effect was via the phosphatidylinositol 3 (PI3)-kinase/Akt pathway because PI3-kinase inhibitors and AKT inhibitors suppressed STS mRNA up-regulation induced by TNFα.…”
Section: Dysregulation Of Steroid Sulfation and Desulfationmentioning
confidence: 95%
See 1 more Smart Citation
“…Because cytosolic β-catenin accumulation induces its translocation into the nucleus, where it interacts with various transcription factors of the TCF family such as TCF4, we determined whether STS increases β-catenin/TCF4 transcriptional activity [ 17 , 19 , 38 – 40 ]. STS expression induced β-catenin accumulation in the nucleus, and the level of cyclin D1, a downstream target of β-catenin, was also strongly increased (Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Suh et al recently reported that TNFα induces STS gene expression through a PI 3-kinase/ Akt signaling pathway in PC-3 human prostate cancer cells. 27) They also described the possible involvement of NF-κB in this induction. However, we found that treatment of SVHK cells with TNFα did not induce any significant increase in STS gene expression (Hattori et al, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%